Coach effectiveness and transformational leadership in sport: the effects of gender and athlete experience / Ahmad Fikri Mohd Kassim and Siti Hasmah Hassan - Mohd Kassim, Ahmad Fikri; Hassan, Siti Hasmah (Universiti Teknologi MARA, Perlis, 2020)
Research has demonstrated the potential importance of transformational leadership and perceived effectiveness of sport coaches for athlete development. Furthermore, coach/athlete's gender and athletes' sport experiences may influence athletes' perceptions of their coach's effectiveness. Researchers to date have not investigated the potential impact of coach/athlete's gender and athlete sport experience on athletes' perceptions of their coach's transformational leadership or replicated the findings of Kavussanu et. al. (2008). Thus, this research explored the coaching efficacy model and transformational leadership theory as the guiding frameworks. Male (n = 150) and female (n = 147) athletes from team (football [n = 49], hockey [n = 53], rugby [n = 51]) and individual (badminton [n = 50], swimming [n = 45], gymnastics [n = 49]) sports completed the coaching effectiveness scale and the differentiated transformational leadership inventory. Multiple regression analyses revealed (a) athlete sport experience did not predict athletes' perceptions of coach effectiveness or transformational leadership, (b) female athletes perceived their coaches to be more effective on all dimensions of coach effectiveness and higher on all dimensions of transformational leadership than male athletes, and (c) coaches were perceived more effective in motivation effectiveness and higher on all dimensions of transformational leadership when they were of the opposite gender to athletes than when gender matched between coach and athlete. In conclusion, coach and athlete gender may have important implications for athletes' perceptions of transformational leadership and coach effectiveness in team and individual sports.